Assessment of Medical Record Documentation and SOAP Completeness in Outpatient Services at a Primary Health Facility - Erwin Hermawan; Erfira Erfira (International Journal of Health and Pharmaceutical (IJHP), 2026)
Medical records are essential for clinical decision-making, continuity of care, legal compliance, and accreditation. Despite their importance, incomplete documentation remains a significant challenge in primary health care, particularly in settings that rely on manual record-keeping. This study assessed the completeness of outpatient medical records at the general polyclinic of Klinik UIN Syarif Hidayatullah Jakarta and examined patterns in outpatient service utilisation, including patient demographics, insurance coverage, and referral trends. A mixed-methods design was employed, integrating quantitative analysis of 399 outpatient medical records from January to February 2024 with qualitative data from observations and interviews. The quantitative component evaluated the completeness of SOAP documentation, patient demographics, service utilisation, and referral rates. The qualitative component investigated workflow challenges, clinician perspectives, and factors influencing documentation quality. In January, 201 outpatient visits were recorded, and in February, 198 visits occurred. Each month, more than 64% of patients were female. BPJS beneficiaries accounted for 842% of all visits, indicating they were the predominant users of the service. Referrals increased from 21 in January to 41 in February, for a total of 62. SOAP documentation was largely complete in January but declined in February, with most omissions found in the Assessment and Objective sections. Fourteen incomplete SOAP components were identified over two months, with 12 occurring in February. Although service utilisation remained stable, documentation quality varied substantially. The frequent incompleteness of the Objective and Assessment components underscores the need for improved workflow organisation, enhanced clinician training, and the adoption of electronic medical records. Regular audits and standardisation of SOAP documentation are recommended to strengthen compliance and support accreditation.